Induksi Mutasi Kara Benguk (Mucuna pruriens L.) Menggunakan Iradiasi Sinar Gamma - Siti Hartati Yusida Saragih; Khairul Rizal; Kamsia Dorliana Sitanggang (Universitas Sebelas Maret, 2020)
Breeding kara benguk with mutation induction techniques using gamma ray radiation is expected to produce genetic diversity. The purpose of the study is to determine the value of Lethal Dose 50 (LD50) and obtain the genetic diversity of the kara benguk plant. The research was conducted at PAIR BATAN and Agrotechnology experiment, Universitas Labuhanbatu from May-July 2020. The planting material used was kara benguk seeds. The method used was Randomized Complete Group Design (RCGD) with one factor which was dose of irradiation with six levels (0, 200, 250, 300, 350 and 400 Gy) and three replications. Each replication consisted of 20 plants, so there are a total of 360 experimental plants. The results showed that the value of LD50 kara benguk in 3 weeks after planting was 281,472 Gy. Gamma ray irradiation increases the high genetic diversity of plants and the number of leaves at a dose of 350 Gy.